AGAINST THE STEREOTYPES OF MUSLIMS AS TERRORISTS IN KARAN JOHAR'S MY NAME IS KHAN: A SOCIOLOGICAL APPROACH - FAIZAH, NUR (2011)
This study aims to show the protest Against the Stereotypes of Muslim as terrorist in Karan Johar's My Name is Khan Movie by using sociological approach. It is done by establishing two parts, the first is analyzing the movie based on its structural elements and the second is analyzing the movie based on the sociology of literature. This research uses descriptive qualitative research. The benefits of this study are to give in the application of Sociological approach in literary study. The primary data is taken from the video and script of My Name is Khan Movie, while the secondary data is taken from book and the information related to theory of sociology. The method of collecting data is library research. The technique of analyzing data is descriptive. The outcome of the study shows that based on the structural analysis it's apparent that in My Name is Khan Movie, Karan Johar conveys a moral message that Muslim is not a terrorist. Based on the sociological analysis, it is evident that in this movie, Karan Johar reflects the social realities of the America society, namely social, political, economic, cultural, science and technology, and religion aspects.